2018
DOI: 10.3390/v10040151
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Recombinant Type 2 Porcine Reproductive and Respiratory Syndrome Virus in China

Abstract: Since the emergence of NADC30-like porcine reproductive and respiratory syndrome virus (PRRSV) in China in 2013, PRRSVs have undergone rapid evolution. In this study, a novel variant of PRRSV strain (designated SCcd17) was successfully isolated from piglets with clinical signs in Sichuan Province in China in 2017, and the complete genomic sequence was determined. The genome of this new isolate was 15,015 nucleotides (nt) long, and comparative analysis revealed that SCcd17 exhibited 90.2%, 85.2%, 84.9%, and 84.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 49 publications
(69 reference statements)
1
21
0
Order By: Relevance
“…The co‐existence of different lineages of PRRSV2 not only complicates the control of PRRSV2 infection in China, but also provides a suitable condition for PRRSV recombination in the field. Distinct recombination patterns between/among different lineages of PRRSV2 were observed in the latest reports (Liu et al., ; Zhou et al., ). In this study, we isolated a novel PRRSV2 variant, denominated SD17‐38, in Shandong province of China in 2017.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…The co‐existence of different lineages of PRRSV2 not only complicates the control of PRRSV2 infection in China, but also provides a suitable condition for PRRSV recombination in the field. Distinct recombination patterns between/among different lineages of PRRSV2 were observed in the latest reports (Liu et al., ; Zhou et al., ). In this study, we isolated a novel PRRSV2 variant, denominated SD17‐38, in Shandong province of China in 2017.…”
Section: Discussionmentioning
confidence: 79%
“…One amino acid deletion at position 34 of GP5 was first found in GZ1101 isolate, which is a RespPRRS MLV‐like virus (Zhou et al., ). The amino acid deletion at position 33 of GP5 was first found in SCcd17, which is a NADC30‐like PRRSV isolate (Zhou et al., ). Here, we first described the SD17‐38 isolate, which simultaneously contains the S/N 33 deletion and N 60 insertion in hypervariable regions of GP5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the C-terminal domain (CTD) is variable among nidoviruses. Besides, nsp10 can vary up to approximately 42% on the amino acid level between the two genotypes, and the strains within PRRSV-2 also vary considerably with amino acid differences as high as 8% [21,22]. We previously reported the first structure of the nidovirus helicase, equine arteritis virus (EAV; family Arteriviridae) nsp10, and demonstrated that the CTD perhaps exerts a regulatory function on the helicase core, facilitating coupling between NTPase and polynucleotide binding activities [23].…”
mentioning
confidence: 99%